2022
DOI: 10.1016/j.caeo.2022.100076
|View full text |Cite
|
Sign up to set email alerts
|

Uses and gratifications of educational apps: A study during COVID-19 pandemic

Abstract: Although educational apps have emerged as an easily available and accessible alternative to classroom learning, particularly at the time of pandemics like COVID-19, no research has attempted to identify learners intentions behind the usage of different educational apps. The current study developed a valid and reliable research instrument to measure the motivations behind using educational apps. Using the mixed method approach commonly used in uses and gratification (U&G) research, i.e., open-ended essays & nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 103 publications
1
14
0
3
Order By: Relevance
“…In contrast with preceding theories that viewed audiences as passive, U&G theory is an audience‐oriented approach (Blumler, 1979; Katz et al., 1973; Rossi, 2002; Rubin, 2009) that views the audience (ie, users) as an active group of people who are consciously selecting their desired media and content to fulfil and satisfy their personal needs and expectations (Katz et al., 1973; Rossi, 2002; Rubin, 2009). Therefore, U&G theory can be considered as an appropriate approach for exploring the needs and expectations of parents and their decision making while selecting educational apps for their children (Menon, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast with preceding theories that viewed audiences as passive, U&G theory is an audience‐oriented approach (Blumler, 1979; Katz et al., 1973; Rossi, 2002; Rubin, 2009) that views the audience (ie, users) as an active group of people who are consciously selecting their desired media and content to fulfil and satisfy their personal needs and expectations (Katz et al., 1973; Rossi, 2002; Rubin, 2009). Therefore, U&G theory can be considered as an appropriate approach for exploring the needs and expectations of parents and their decision making while selecting educational apps for their children (Menon, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Identifying gender differences is relatively easy, but proper explanation of gender differences requires a mixed‐methods approach that allows sense to be made of the findings (eg, interviews, focus groups, self‐reports, questionnaires, Heidari et al., 2016). In a recent study, Menon (2022) used a mixed‐methods approach to examine the role gender played in moderating learners' gratifications (eg, academic assistance, social influence, and convenience) when using educational apps. Their quantitative data revealed that the intention to use educational apps differs among male and female students while their qualitative data provided meaning to these differences.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital competence is the ability of an individual to respond to the digital environment technically, ethically, and cognitively. Previous studies focused on the motivational satisfaction that individuals feel regarding metaverse technology and its contents [27,35], but this study focused on metaverse utilization motives according to the level of individual digital competence. As a result, this study has academic implications in terms of confirming that the level of digital competence possessed by metaverse users can affect an individual's digital experience.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Researchers have used the uses and gratifications theory to comprehend different phenomena, including the motives for using social networking sites (Pai & Arnot, 2013), smartphones (Park et al, 2013), tablets (Magsamen-Conrad et al, 2015), and educational apps during COVID-19 pandemic (Menon, 2022). However, most researchers have utilized the uses and gratifications theory when studying the news consumption phenomenon (Lee & Chyi, 2014).…”
Section: Uses and Gratifications Theorymentioning
confidence: 99%